Safety of Off-Label Pharmacological Treatment in Pediatric Neuropsychiatric Disorders: A Global Perspective From an Observational Study at an Italian Third Level Children’s Hospital - Giurin, Maria Sole; Trojniak, Marta Paulina; Arbo, Anna; Carrozzi, Marco; Abbracciavento, Giuseppe; Monasta, Lorenzo; Zanus, Caterina (Frontiers in Pharmacology, 2022)
Background The acquisition of proper and relevant pediatric clinical data is essential to ensure tolerable and effective pediatric drug therapies. In the field of pharmacological treatment of neuropsychiatric disorders, the lack of sufficient high quality scientific evidence for pediatric age results in the frequent need to prescribe off-label drugs. With the aim of improving knowledge about safety profile of off-label drug prescription in children and adolescent with neurological and/or psychiatric disorders, we realized a multidisciplinary pharmacovigilance study. Materials and methods An observational retrospective study was conducted to assess the safety of off-label pharmacological therapies in patients aged 0-18 years, admitted to the Neuropsychiatry Unit of the Institute for Maternal and Child Health - IRCCS "Burlo Garofolo" between January 2016 and December 2018. Prescription patterns and adverse drug reactions (ADRs) were evaluated by a multidisciplinary team. Results Overall, 230 patients were enrolled, 48 % boys (N = 111), 52% girls (N = 119), average age of 10 years, and a total of 534 prescriptions was analyzed. 54.5% (N=125) of patients had epilepsy, 37.5% (N=86) suffered from psychiatric disorders, 8% (N=19) had other neurological disorders. The prevalence of off-label prescriptions was 32% and 50% of the study population received at least one off-label drug. A total of 106 ADRs was detected: 57% of ADRs were due to drug-drug interaction, 30% were due to off-label prescriptions, 10% were due to overdose and 3% were due to improper use. No significant association between emerged ADRs and off label prescriptions was found (Fisher’s exact two-tailed test, p=1.000). There was significant association between increasing number of administrated drugs and risk of ADRs (OR 1.99; IC95% 1.58-2.5; p = 0.000). Psychiatric disorders were associated with at least three times higher risk to be treated with an off-label drug (OR 3.30; IC95% 2.26-4.83; p=0.000). Conclusions This study shows that off-label prescribing in neuropsychiatric disorders does not pose a greater risk of ADRs than on-label prescribing and highlights unmet clinical needs in pediatric neuropsychopharmacology. The multidisciplinary approach can provide important contributions to improve therapeutic path of these already complex pathologies by careful monitoring of therapeutic appropriateness and drug interactions.